Mechanochemical patternable ECM-Mimetic hydrogels for programmed cell orientation - Lavrador, Pedro (2022)
Native human tissues are supported by a viscoelastic extracellular matrix (ECM) that can adapt its intricate network to dynamic mechanical stimuli. To recapitulate the unique ECM biofunctionality, hydrogel design is shifting from typical covalent crosslinks toward covalently adaptable networks. To pursue such properties, herein hybrid polysaccharide-polypeptide networks are designed based on dynamic covalent assembly inspired by natural ECM crosslinking processes. This is achieved through the synthesis of an amine-reactive oxidized-laminarin biopolymer that can readily crosslink with gelatin (oxLAM-Gelatin) and simultaneously allow cell encapsulation. Interestingly, the rational design of oxLAM-Gelatin hydrogels with varying aldehyde-to-amine ratios enables a refined control over crosslinking kinetics, viscoelastic properties, and degradability profile. The mechanochemical features of these hydrogels post-crosslinking offer an alternative route for imprinting any intended nano- or microtopography in ECM-mimetic matrices bearing inherent cell-adhesive motifs. Different patterns are easily paved in oxLAM-Gelatin under physiological conditions and complex topographical configurations are retained along time. Human adipose-derived mesenchymal stem cells contacting mechanically sculpted oxLAM-Gelatin hydrogels sense the underlying surface nanotopography and align parallel to the anisotropic nanoridge/nanogroove intercalating array. These findings demonstrate that covalently adaptable features in ECM-mimetic networks can be leveraged to combine surface topography and cell-adhesive motifs as they appear in natural matrices.